Perception of foreign students on food safety and hygiene practices among food handlers in Malaysian restaurants: public health perspective. - Olumide Adedokun Odeyemi, (Universiti Kebangsaan Malaysia, 2013)
Influx of foreign students in Malaysia calls for a study on safety of food in Malaysia restaurants as perceived by them.